Evolutionary analysis of TIR- and non-TIR-NBS-LRR disease resistance genes in wild strawberries - Zhu, Ni; Feng, Yuxi; Shi, Guangxin; Zhang, Qihang; Yuan, Bo; Qiao, Qin (Frontiers in Plant Science, 2024)
The NBS-LRR genes (NLRs) in plants represent the most extensive category of plant resistance genes (R genes) and are crucial for defending against pathogens. In this study we conducted a comprehensive genome-wide identification, structural analysis, and evolutionary investigation of NLRs across eight diploid wild strawberries. The results revealed that the Non-TIR-NLRs (non-TNLs) account for over 50% of the NLR gene family, surpassing the proportion of TIR-NLRs (TNLs) in all eight strawberry species. The phylogenetic tree indicated that TNLs diverged into two subclades: one grouping with CC-NLRs (CNLs) and the other closely related to RPW8-NLRs (RNLs). Furthermore, the number of non-TNLs under positive selection is significantly higher than that of TNLs, suggesting rapid diversification of non-TNLs in strawberries. We further examined the gene structure and expression level across different NLR subfamilies. Our analysis revealed that non-TNLs, which have shorter gene structures compared to TNLs, showed higher expression levels, particularly highlighting the expression of RNLs. Notably, non-TNLs displayed obvious expression dominance under both normal and infected conditions. Finally, we performed in vitro leaf inoculation assays with Botrytis cinerea to evaluate the resistance among various diploid strawberry species. The results indicated that F. pentaphylla and Fragaria nilgerrensis, which have the highest proportion of non-TNLs, exhibit significantly greater resistance to B. cinerea compared to Fragaria vesca, which has the lowest proportion of non-TNLs. Our research sheds light on the evolution of disease resistance genes in strawberries and their potential applications in breeding for disease resistance.